The Philosophy of Habis Adat Karena Mufakat: Consensus of Diversion of Pusako Tinggi in Minangkabau (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
Minangkabau people own non-transferable pusako tinggi. Selling it means the abolition of people’s wealth, resulting in the disappearance of Sako and Pusako. A portion of pusako tinggi no longer belongs to the native as it is transferred to other parties. This study aims to explore the philosophy of pusako tinggi in Minangkabau and the consensus on its diversion. Primary data were collected through interviews and documentation. Interviews were conducted with representatives of those who donated the pusako tinggi. Secondary data were obtained from books, journals, and others. Data were analysed through display, reduction, and verification techniques. This study found that the land is not a mere symbol but represents the existence and dignity of the civilised Minangkabau society. Pusako tinggi in Minangkabau community consensus can be transferred when dealing with crucial customary and religious interests. The reality shows that Minangkabau community baradat kareh, baugamo kuaik (adhere to customs and religion)
Keywords: Customs; Philosophy; Minangkabau; Pusako Tinggi